Gaya Kepemimpinan Kepala Madrasah Dalam Membentuk Karakter Siswa - Masruroh, Durrotul (Global Education Journal, 2023)
The development of increasingly sophisticated technology and the lack of supervision from parents of children have a major impact on the formation of student character. Various kinds of social media that are now favored by students and teenagers and the existence of online game games that can divert students to learn are the main obstacles that must be faced by educators in schools. Especially for madrasah heads who have great responsibility for institutions and institutional communities. This study aims to examine the leadership style of the head of the madrasah in shaping the character of students. By using literature research, based on the results of the research is important to have a charismatic Madrasah head in shaping student character, Because with charismatic leaders, students become motivated and inspired to develop their good character. The leadership style of the head of the madrasah varies, namely: Charismatic / Charismatic, Autocratic / Autocratic, Democratic / Democratic, Bureaucratic / Bureaucratic, Transactional, Transformational, and Laissez-Faire / Free Leadership. However, the leadership style that is often used by madrasah leaders in shaping student character is the charismatic leadership style.